Attitudes Toward Learning and Investment in Employee Development in Sport Organisations - Laninovic, Dejan (Digital Repository of Theses, 2024)
Sport, a global phenomenon, encompasses a vast market valued at $388.3 billion in 2020, projected to reach $599.9 billion by 2025. Managing the sport business, laden with unique attributes, requires adept handling of perishability, unpredictability, and the intersection with various industries. A critical factor in the success of sport organizations is their human resource. However, little research has been directed towards learning readiness and managerial attitudes towards employee development within sports organizations. This study delves into the readiness of employees to learn and the attitudes of managers towards learning in sports organizations. As 90% of companies reshape jobs and automate roles, the workforce faces significant challenges. While many organizations prefer re-skilling their existing workforce, sports organizations lag in allocating consistent budgets for employee training. The research aims to address this gap by investigating the attitude of managers towards learning, the readiness of employees to learn, and the investment in employee development within the unique context of sports organizations. The theoretical foundation emphasizes the value of employee development, highlighting the symbiotic relationship between organizational success and employee growth. Acknowledging the shift from viewing organizations merely as task-oriented entities to intelligent systems managing knowledge the research seeks to explore the specificities of sports organizations. The research will employ primary quantitative methods, utilizing online questionnaires to assess employee learning readiness and managerial attitudes towards learning. The study will be conducted in Switzerland within international sports organizations and Croatia within national and club-level sports organizations. The data will be analyzed using SPSS software, incorporating descriptive statistics. In addressing a void in the literature, this research contributes to the understanding of employee development and attitudes towards learning in the unique context of sports organizations. The findings aim to inform strategic decisions, fostering a culture of continuous learning, and ensuring the long-term success and prosperity of sports organizations in an ever-evolving landscape.